A fuzzy logic controller for a hydrostatic transmission for an electric hybrid bus in Bogotá (2016)
The control strategy in a hydraulic hybrid vehicle is very important for taking advantage of its full potential. In a hydraulic hybrid vehicle, the hydrostatic transmission can be controlled in order to optimize the entire system. A hydrostatic transmission is composed basically of a hydraulic motor and a hydraulic pump. For an electric hybrid vehicle an electric motor is the prime mover. In this study the control variables are the displacements of the hydraulic devices and the objective is to optimize the system efficiency. All possible combinations of displacements were tested through simulation and the most efficient combination was recorded. Around 9% of the energy can be saved using the most efficient configuration of the hydrostatic transmission. Fuzzy logic theory was used to simulate the driver input and proposed as a control strategy for the hydrostatic transmission